Utilisation of primary and secondary G-CSF prophylaxis enables maintenance of optimal dose delivery of standard adjuvant chemotherapy for early breast cancer: An analysis of 1655 patients - Chan, Arlene; McGregor, S.; Liang, Wenbin (Churchill Livingstone, 2014)
Optimal outcome for early breast cancer patients receiving adjuvant chemotherapy requires adequate dose delivery, commonly defined as >85% of planned dose of chemotherapy agents. Outside the clinical trial setting, reports from community oncology centres have demonstrated that a significant proportion of patients fail to receive this dose intensity, with neutropenia being the most commonly cited reason for sub-optimal treatment. Data collected prospectively on 1655 patient treated in a single breast cancer centre demonstrates that patients at risk of sub-optimal dose delivery can be identified by routine assessment of neutropenic events during the first cycle. The uniform administration of secondary G-CSF for all subsequent cycles enables dose delivery ≥85%, which was shown to lead to improved survival outcomes when compared with those patients who received <85%.